المجندون الجزائريون في الجيش الفرنسي خلال الحرب العالمية الأولى ضمن كتابي الملازم عبد الله بوكابوية - محتالي دنيا; ستي ناجية; خرفي اسيه (University Of Eloued جامعة الوادي, 2026)
"أدركت فرنسا الاستعمارية مع اندلاع الحرب العالمية الأولى حاجتها الملحة للموارد البشرية والمادية من مستعمراتها، خاصة الجزائر التي أولت لها أهمية كبرى، فعمدت إلى تجنيد شبابها في سبيل قوتها العسكرية، مستعملة شتى الوسائل والأساليب، ورغم سياسة الرفض والعراقيل المختلفة، إلا أنها مارست ساسة الترغيب والترهيب في حق المجندين، الذين قدموا الكثير من التضحيات في حرب لا تعنيهم، رغم المعاناة والآلام عبر عديد الجبهات أوقد استخلصوا العديد من النتائج. كما تطرقنا لإبراز معاناة المجندين الجزائريين في الجيش الفرنسي من خلال كتابات عبد الله بوكابوية والظروف الصعبة التي واجهها المجندون، بما في ذلك التمييز العنصري الذي تعرضوا له، والمعاملة السيئة، وعدم الاهتمام الكافي بهم كمقاتلين. كما تناولنا لهروب والتحاق بوكابوية بمعسكر الهلال الألماني من خلال كتاباته التي تروي كيف تمكن بوكابوية من الفرار من الجيش الفرنسي في أفريل1915م برفقة نحو سبعين من رفاقه، والتحاقهم بمعسكر الهلال الألماني في برلين.هذا المعسكر كان مخصص للأسرى المسلمين. كما بينا الدور الدعائي لبوكابوية بعد هروبه، لعب دورا دعائيا كبيرا لصالح ألمانيا والدولة العثمانية، كان يقوم بإلقاء الخطب والمحاضرات أمام الأسرى المسلمين، ويوزع المنشورات، ويؤلف الكتيبات التي تدعو الجزائريين والمسلمين بشكل عام إلى الانضمام ‘لى ألمانيا و الدولة العثمانية ضد فرنسا، مستغلا فكرة ''الجهاد'' ضد المختلين. بالإضافة إلى تركز بوكابوية في كتاباته على الجانب الديني، ويفصل كيفية معاملة الجيش الفرنسي للمجندين المسلمين فيما يتعلق بشعائرهم الدينية مثل الصلاة والصوم والطعام والشراب، مبرزا التناقضات والانتهاكات التي حدثت. وفي هذه الورقة البحثية ارتأينا أن نسلط الضوء على تأثير الحرب على المجندين، خاصة والمجتمع الجزائري عامة والتطرق إلى أهم الأدوار، والمهام المسندة إليهم،ونتائج ذلك، معتمدين في هذا الصدد على المنهج الوصفي والتحليلي لوصف الحقائق وتدوينها. كما أردنا أن نقدم من خلال كتابات الملازم رابح بوكابوية منظورا داخليا لواقع المجندين الجزائريين في الحرب العالمية الأولى،وتسلط الضوء على معاناتهم، ودورهم في الصراع، وكيف أصبحت قضيتهم جزءا من صراع دعائي أوسع بين القوى المتجاربة. "Abstract With the outbreak of World War I, colonial France realized its urgent need for both human and material resources from its colonies, especially Algeria, to which it gave great importance. France resorted to conscripting Algerian youth to strengthen its military power, employing various means and methods. Despite the resistance and the numerous obstacles, it implemented both persuasive and coercive policies against the recruits, who made significant sacrifices in a war that was not theirs. They endured suffering and hardship on many fronts, yet drew numerous conclusions from their experience. This study also highlights the suffering of Algerian recruits in the French army, as documented in the writings of Abdullah Boukabouya. His accounts reveal the difficult conditions the recruits faced, including racial discrimination, poor treatment, and a general lack of care and recognition as legitimate combatants. We also addressed Boukabouya's escape and his joining of the German “Half Moon Camp” through his own writings, which recount how he managed to flee the French army in April 1915 with about seventy of his comrades and join the Half Moon Camp in Berlin, a facility dedicated to Muslim prisoners of war. After his escape, Boukabouya played a significant propaganda role in favor of Germany and the Ottoman Empire. He gave speeches and lectures to Muslim prisoners, distributed pamphlets, and authored booklets urging Algerians and Muslims in general to join Germany and the Ottoman Empire against France, invoking the concept of “jihad” against the occupiers. Boukabouya’s writings also focused heavily on religious aspects, detailing how the French army treated Muslim recruits in matters such as prayer, fasting, food, and drink, exposing the contradictions and violations that occurred. In this research paper, we aimed to shed light on the impact of the war on both the Algerian recruits and the broader Algerian society. We also examined the key roles and responsibilities assigned to them, and the resulting outcomes, relying on the descriptive and analytical methodology to document and interpret the facts. Furthermore, through the writings of Lieutenant Rabah Boukabouya, we sought to present an internal perspective on the reality of Algerian recruits during World War I, highlighting their suffering, their role in the conflict, and how their cause became part of a broader propaganda struggle among the warring powers.
مذكرة ماستر قسم علوم الاسلامية تخصص تاريخ المغرب العربي معاصر
Keywords: معسكر الهلال الألماني; الأسرى المسلمون; الدعاية الألمانية; الدولة العثمانية; عبد الله بوكابوية; المجندون الجزائريون; الجيش الفرنسي; الحرب العالمية الأولى; التجنيد; Keywords: Conscription; World War I; French Army; Algerian Recruits; Abdullah Boukabouya; Ottoman Empire; German Propaganda; Muslim Prisoners; Half Moon Camp.